2017
DOI: 10.6023/cjoc201703020
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances on the C-H Bond Functionalization on C(5) Position of 8-Aminoquinolines

Abstract: 8-Aminoquinolines are important nitrogen-containing heterocycles widely existing in the natural products, bio-active molecules and agrochemicals. It has been developed as significant bidentate directing groups or as ligand auxiliary in various kinds of organic reactions, especially in the area of C-H bond functionalization. Therefore, the synthesis of such motifs, especially those with substituted quinolines is of great significance. This review focuses on the remote C-H bond functionalizaitons of 8-aminoquino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Recent years have witnessed much progress in halogenation reactions of the quinoline ring in the C2–C7 positions [ 8 9 ]. Among them, the synthesis of important C5-halogenated products gained particular attention since Stahl et al reported the first chlorination example using LiCl as the halogen source [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have witnessed much progress in halogenation reactions of the quinoline ring in the C2–C7 positions [ 8 9 ]. Among them, the synthesis of important C5-halogenated products gained particular attention since Stahl et al reported the first chlorination example using LiCl as the halogen source [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“… 11 Since Stahl et al 12 reported the first instance of cuprous-catalyzed chlorination using lithium chloride in an oxygen atmosphere, remote C5-functionalization has garnered particular interest. 13 Recent efforts have been focused on C–C, 14 C–N, 15 C–P, 16 C–O, 17 C–S 18 and C–X 19 bond construction through direct C5-H functionalization via transition-metal-catalyzed reactions as well as by employing metal-free conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, as part of our continuous works on the development of cross-coupling reaction utilizing Grignard reagents as key coupling partner as well as on the functionalization of aminoquinoline, we disclose an efficient protocol for site-selective cleavage of C­(O)–CF 3 bond of a wide range of trifluoroacetyl amides by Grignard reagents (Scheme b2). Trifluoroacetanilides, 2,2,2-trifluoro- N -(quinolin-8-yl)­acetamide and N -alkyl-2,2,2-trifluoroacetamide are well tolerated in this protocol.…”
Section: Introductionmentioning
confidence: 99%